Neutrino interactions on nuclei at MINERvA - Carneiro, MF (2015)
Here we present analysis results from the MINERvA experiment for scattering of neutrinos on nucleus in an energy region of few GeV. These results cover a plethora of processes important for high precision neutrino oscillation measurements in which recent results have suggested that the currently used models are insufficient.